Forest hoverfly community collapse: Abundance and species richness drop over four decades. Issue 5 (12th April 2022) - Barendregt, Aat; Zeegers, Theo; van Steenis, Wouter; Jongejans, Eelke
Abstract: To study insect decline, an important threat to biodiversity, long‐term datasets are needed. Here we present a study of hoverfly (Diptera: Syrphidae) abundance and diversity in a Dutch forest, surrounded by other forests, and analyse the variation in insect numbers over four decades. Between 1982 and 2021, abundance decreased by 80%. Until 1990, abundance showed a strong decrease of 10.9% per year, mainly in nationally rare species with carnivorous larvae exposed to air. From 1990, abundance stabilised, whereas from 2000, a second period of strong decline of 9.0% per year occurred, mainly in very common species. Species richness also declined strongly between 1979 and 2021: the total number of species observed in five monitoring days dropped by 44% over those 43 years. The characteristic set of dry‐forest hoverfly species disappeared over four decades. The number of nationally rare species observed at the study site declined from 19 to 9 early on, in a period (1979–1984) that coincided with intense nitrogen input and acidification caused by agriculture in the same region. The more recent decline is likely also caused by factors from outside the forest, as forest management and conditions remained constant. Continued influx of nutrients and pesticides at a regional level, as well as climate change are possible causes of the decline. Research is needed to quantify their relative effects. Abstract : In a Dutch forest, the abundance of hoverflies decreased by 80% between 1982 and 2021: until 1990 with 10.9% per year, in 1990–2000 numbers stabilised, and from 2000 a decline of 9.0%. Species richness declined strongly between 1979 and 2021: the total number of species observed on five monitoring days dropped by 44%. The number of nationally rare species observed declined from 19 to 9 in 1979–1984; by 2021 the characteristic set of dry‐forest species had disappeared, and only some common hoverflies remain.